Exploring graduates experiences and perceptions of the Postgraduate Diploma in Addictions Care between 2012 and 2018 at the University of Cape Town - Allie, Shaheema (Department of Psychiatry and Mental Health, 2025)
Background: To address the training needs for addiction specialists to detect and treat the growing number of individuals using alcohol and drugs, there is a need to upscale existing quality academic programmes to implement evidence-based practices (EBPs) widely. It is vital that professionals in addictions services are well equipped to handle the burden of unhealthy substance use. Aims and objectives: The overall aim is to investigate students' knowledge, attitudes and explore experiences related to EBP approaches taught in the Postgraduate Diploma in Addictions Care (PgDip) at the University of Cape Town (UCT). The specific objectives included: (1) assessing the attitudes and perceived knowledge gained by students related to EBP approaches taught on the PgDip programme, (2) exploring the experiences of graduates in integrating EBP taught on the PgDip programme into substance use services as part of their occupation, and (3) eliciting graduates' recommendations on how the PgDip programme can be improved. Methods: This mixed methods study recruited participants registered for the PgDip at UCT between 2011 and 2018. Participants (n=113) were invited to partake in the online quantitative questionnaire which assessed attitudes towards EBP approaches, knowledge retention of EBP approaches and EBP skills used in their current occupation. The measures included questions on socio-demographics, occupation and use of skills, participants' satisfaction with the PgDip and the Evidence-Based Practice Attitudes Scale (EBPAS). Descriptive statistics and ANOVA were conducted using SPSS. The qualitative online in-depth semi-structured interviews (n=20) addressed graduates' opinions on the programme, retention of knowledge, skills, and recommendations for improving the PgDip. Additionally, it explored the impact of the PgDip on their career paths, daily practice, and challenges and facilitators to implementing EBP in their organisations. Transcripts were uploaded into NVivo and analysed using thematic analysis. Results: 54 (47.8%) participants completed the online questionnaire with an overall positive attitude towards EBPs and satisfaction with the PgDip programme. There was with no statistical difference found between the year of graduation and screening and intervening for SUD (p= 0.52 and 0.93). 49 (91%) participants across occupational/occupational groups reported that they have been able to implement EBP in their workplace. For the EBPAS, the average total score was 42.85 (SD=6.55). The mean scores for the EBPAS subscales were as follows: the Appeal subscale score was 3.18 (SD=0.62), the Openness subscale was 3.22 (SD=0.57), the Divergence subscale was 2.40 (SD=0.92), and the Requirement subscale was 2.55 (SD=1.11). There were no statistically significant difference in mean scores for any of the four EBPAS subscales between the three profession/occupation groups. Qualitatively, all graduates were satisfied with their overall academic experience on the PgDip, attitudes were generally positive towards EBP, and they retained EBP knowledge gained on the programme, and many transferred this knowledge to their organisations. The main barriers were competing with bureaucratic management styles of organisations, pressure on existing resources and working in a multidisciplinary team. Completing the PgDip also had a positive impact on career progression. Conclusion: EBPs learnt on the PgDip seemed to have long-lasting positive effects for graduates, which were perceived as being beneficial to their context and organisation.